Exploratory analysis of biomarkers associated with clinical outcomes from the study of palbociclib plus endocrine therapy in premenopausal women with hormone receptor-positive, HER2-negative metastatic breast cancer - Soohyeon Lee; Kyunghee Park; Gun Min Kim; Kyung Hae Jung; Seok Yun Kang; In Hae Park; Jee Hyun Kim; Hee Kyung Ahn; Woong-Yang Park; Seock-Ah Im; Yeon Hee Park (Breast, 2022)
Background: Palbociclib plus endocrine therapy (ET) demonstrated significant progression-free survival (PFS) benefit in Young Pearl, a randomized phase ll trial comparing palbociclib + ET versus capecitabine in premenopausal women with hormone receptor positive, HER2 negative metastatic breast cancer (MBC). This exploratory analysis investigated potential biomarkers of palbociclib plus ET on PFS. Patients and methods: Of 178 patients randomized (92 palbociclib plus ET; 86 capecitabine), we performed targeted sequencing (141 patients) and whole transcriptome sequencing (165 patients) using baseline tumor samples to examine genomic alteration in relation to drug response on PFS. Hazard ratios (HRs) were estimated using unstratified Cox proportional hazards models. Results: PIK3CA (41%) and TP53 (33%) mutations and CCND1 copy number variation (29%) were found most frequently in targeted sequencing of 141 patients. ESR1 mutations were found only in 3.5% of patients of this population. Luminal type showed better prognosis in palbociclib + ET arm but no impact on PFS difference in capecitabine arm. High TMB, TP53 mutation, PTEN loss of function mutation and RB1 pathway alteration showed worse prognosis in palbociclib plus ET arm. Patients with BRCA2 pathogenic mutations showed worse prognosis regardless of PAM50 subtypes. AURKA mutation/amplification, BRIP1/MYC/RAD51C amplification were significantly associated to the patients with short PFS <6 month. Conclusion: Of palbociclib plus ET, luminal type showed better prognosis and BRCA2 pathogenic mutation showed worse prognosis regardless luminal/non-luminal type. Further exploration of molecular variables is warranted to determine and validate biomarkers of efficacy and resistance.